Mães enfermeiras : o processo de cuidado dos filhos no contexto de vida e trabalho - Rodrigues, Bruna Caroline (2012)
Due to the financial demands and to the transformations undergone by our contemporary society as well, parents spend the majority of their day away from home, leaving their children in the care of grandparents, babysitters and preschools. It is common that this change in the family dynamics ends up generating a sense of frustration among mothers regarding the full exercise of their maternal role. Nursing itself has a feminine representation as it is a profession that has as its core the act of caring and offering affection to the others. This aforementioned fact is directly linked to the role of being a mother, who takes care, nurtures and educates. Thus, this study aims to understand the process of taking care of children in the life of nurses which are mothers. This is a descriptive exploratory study with a qualitative approach which was conducted with 10 nurses who are mothers dwelling in the city of Maringá, Paraná Sate. The data collection and the selection of participants was made through the snowball method. According to this search strategy, the first interviewee indicates the second, which in turn indicates the third, and so on. The data collection was done from November, 2011 to January, 2012 throughout interviews using a semi-structured questionnaire developed by the researcher. In order to register in a didactic fashion the information regarding the social support network for the participant families, a genogram and an eco-map was made. The collected data underwent a descriptive and an analytical study taking into account the content analysis theory of Bardin. The results revealed the difficulties experienced by nurses who are mothers in conciliating their social roles, especially in the process of caring for and educating their children. Despite the couple's effective participation in the parenting, the mothers feel the need for a greater amount of time to spend with their children. Moreover, it was observed that the return to work was pointed as the main cause for the premature weaning, causing some frustration among such mothers for failing to implement the recommendation of exclusive breastfeeding until the baby is six months old in terms of his personal experience. It was found that the family role, as well as the partner support in the process of becoming a mother appear as key elements to the full development of the various aspects or areas of these women's lives. In this perspective, and also valuing the mother-child relationship as a unique opportunity to emotional exchange, as well as the main source of happiness in their lives, the participants highlighted the importance of their professional activity in the design of their personal fulfillment. It was considered that women suffer from internal pressures related to the fact that they are nurses and, due to that, overvalue the proper care which should be given the children, which is not always possible to implement in their own lives. In this sense, it should be further noted that the delegation of responsibilities should be carried out in a way that the outsourcing of children care obeys very specific necessity criteria and that it cannot be trivialized to the point of compromising a so precious link as the one uniting mothers to their children.